2001
DOI: 10.1002/1099-0690(200111)2001:22<4189::aid-ejoc4189>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Heck Reactions of Ethenyl- and (Z)-Butadien-1-yl Nonaflate Obtained by the Fragmentation of Furan Derivatives

Abstract: Keywords: Carbanions / Silyl enol ether / Fluorides / Alkenyl nonaflates / Heck reactionThe nonaflation of lithium enolates or of silyl enol ethers, formally derived from acetaldehyde or crotonaldehyde, with nonafluorobutanesulfonyl fluoride gave ethenyl nonaflate (1b) and (Z)-buta-1,3-dien-1-yl nonaflate (2) in good yields. The required enolates were obtained by aldehyde-free routes by the lithiation of tetrahydrofuran or 2,5-dihydrofuran followed by the cyclofragmentation of the metallated heterocycles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Rather the product from an apparent 1,2‐migration of the intermediate alkenyl palladium(II) species was obtained in good yield (79 %; Table 2, entry 1) 15. This result is in stark contrast to recent observations by Reissig and co‐workers, in which the Heck coupling between the corresponding vinyl nonaflate and methyl acrylate under phosphane‐free conditions was reported to give the expected coupling product 12c. Nevertheless, coupling of the same vinyl tosylate with a variety of alkenes revealed this isomerization to be quite effective with yields attaining 95 % and with exclusive trans selectivity in all but one case (Table 2, entries 2–6).…”
Section: Methodscontrasting
confidence: 65%
“…Rather the product from an apparent 1,2‐migration of the intermediate alkenyl palladium(II) species was obtained in good yield (79 %; Table 2, entry 1) 15. This result is in stark contrast to recent observations by Reissig and co‐workers, in which the Heck coupling between the corresponding vinyl nonaflate and methyl acrylate under phosphane‐free conditions was reported to give the expected coupling product 12c. Nevertheless, coupling of the same vinyl tosylate with a variety of alkenes revealed this isomerization to be quite effective with yields attaining 95 % and with exclusive trans selectivity in all but one case (Table 2, entries 2–6).…”
Section: Methodscontrasting
confidence: 65%
“…It was observed that the coupling was influenced by the presence of lithium chloride as the co-catalyst, the product (3 E , 5 Z )-octa-3,5,7-trien-2-one ( 15 ) was obtained in good yields and high ( E )-selectivity. In fact as expected, nonaflate 14 seemed to react while retaining its configuration as illustrated in Scheme 8 [ 15 ].…”
Section: 13-dienessupporting
confidence: 64%
“…The substrate was reacted with the alkyl acrylates 12a (R 1 = Me) and 12b (R 1 = t- Bu) under phosphine-free conditions [3334] using 6 mol % of palladium(II) acetate, triethylamine as base and lithium chloride [35] leading to the expected coupling products syn - 13 and syn - 14 in 39% and 82% yield, respectively (Scheme 5). In both cases, only the E -configured 2-substituted alkyl acrylates were isolated.…”
Section: Resultsmentioning
confidence: 99%